PELUANG USAHA INOVASI PUPUK TULANG TERNAK DAN CANGKANG TELUR UNTUK PERTANIAN BERKELANJUTAN - Ratih Apri Utami; Anarofida Anarofida; Meihilda Hoda Pratiwi; Rizky Bangkit Pamungkas; Sapna Dwi Elisa; Ubaidillah Ubaidillah (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
Food is one of the needs consumed by humans every day to support survival. Food consumed by humans certainly produces waste from unused food waste. The existence of livestock bones and egg shells that are abundant in the community as food waste from animal materials can be used for organic fertilizer. The effective content of the waste can support the completeness of fertilizer nutrients applied to plants. "PTC Organik" is here as a pioneering innovation in quality waste fertilizer from a combination of cow, chicken, and eggshell bone meal in order to support sustainable agriculture as well as food security due to the scarcity of subsidized fertilizers. The objectives of this program are 1) creating a diversification of organic fertilizers; 2) providing sustainable and environmentally caring organic fertilizer needs; and 3) foster an entrepreneurial spirit. The method of sales is carried out directly as well as indirectly. Product sales have been carried out from August to September 2022, where "PTC Organik" products were sold as much as 85 pcs with a weight of 500 grams each, revenue of Rp. 1,800,000,-, a profit of Rp. 471,508,-. While the BEP price is Rp. 24,000 and the BEP of the product is 47 pcs and B/C Ratio 1,28. Based on this, the product business "PTC Organik" indicates the potential to be developed.